A phase III double-blind, placebo-controlled, randomized withdrawal trial of 5‑aminolevulinic acid hydrochloride with sodium ferrous citrate for efficacy and safety in patients diagnosed as Leigh syndrome - Akira Ohtake; Yuichi Abe; Kei Murayama; Hideaki Shiraishi; Hitoshi Osaka; Satoko Kumada; Tetsuya Ito; Hidehito Kondo; Yusuke Hamada; Sayaka Suzuki-Ajihara; Masato Arao; Yuki Ueda; et al. (PLoS ONE, 2026)
Objective A phase III, double-blind, placebo-controlled, randomized withdrawal trial of SPP‑004 (5‑aminolevulinic acid hydrochloride and sodium ferrous citrate) was conducted to confirm the efficacy and safety of SPP-004 for maintenance of clinical response in patients diagnosed with Leigh syndrome (LS) showing central nervous system disorders. Methods Fifty-four patients entered a 24-week open-label period of SPP-004 administration. Among them, 28 patients who showed improvement on the Newcastle Paediatric Mitochondrial Disease Scale (NPMDS) for cranial nervous symptoms and myopathy symptoms proceeded to a 48-week double-blind (DB) period, where they were randomized (1:1) to receive SPP‑004 or placebo ( n = 14 each). Efficacy was evaluated using NPMDS for the full analysis set (FAS) during the DB‑period (SPP-004 n = 13, Placebo n = 14) and the entire study period ( n = 54). Safety evaluation focused on adverse events (AEs) in all 54 patients administered SPP-004. Results The primary endpoint, the proportion of patients who discontinued due to inadequate efficacy at 48 weeks, was lower in the SPP-004 group (15.4% [95% CI: 1.9–45.4%]) compared to the placebo group (50.0% [23.0–77.0%]). Over 80% of the SPP-004 group showed maintained efficacy (p = 0.0486). All adverse drug reactions were mild, with no notable differences in AEs between groups. Conclusion These findings suggest that SPP-004 is safe and may provide therapeutic effect for LS patients who achieved an initial clinical response.